Formation of Etch Pits on Germanium Surfaces Loaded with Reduced Graphene Oxide in Water. (25th April 2017) - Nakade, Kazuki; Hirano, Tomoki; Li, Shaoxian; Saito, Yusuke; Mori, Daichi; Morita, Mizuho; Kawai, Kentaro; Arima, Kenta
Abstract : Graphene oxide (GO) was reduced by either a thermal treatment in Ar ambient or a chemical process using hydrazine monohydrate. A Ge surface loaded with reduced GO (RGO) was immersed in water containing dissolved O2 molecules. We demonstrated that etch pits were formed by the immersion, whose shape depended on the initial form (particles or dispersed sheets) of RGO on Ge. We speculate that a Ge surface in contact with RGO is selectively etched in water by the catalytic activity of RGO, which enhances the oxygen reduction reaction.